Genome assembly resources of genitourinary cancers for chromosomal aberration at the single nucleotide level - Hyunho Han; Hyung Ho Lee; Min Gyu Kim; Yoo Sub Shin; Jin Soo Chung; Jun Kim (Scientific Data)
Abstract Traditionally, the evolutionary perspective of cancer has been understood as gradual alterations in passenger/driver genes that lead to branching phylogeny. However, in cases of prostate adenocarcinoma and kidney renal cell carcinoma, macroevolutionary landmarks like chromoplexy and chromothripsis are frequently observed. Unfortunately, short-read sequencing techniques often miss these significant macroevolutionary changes, which involve multiple translocations and deletions at the chromosomal level. To resolve such genomic dark matters, we provided high-fidelity long-read sequencing data (78–92 Gb of ~Q30 reads) of six genitourinary tumour cell lines (one benign kidney tumour and two kidney and three prostate cancers). Based on these data, we obtained 12 high-quality, partially phased genome assemblies (Contig N50 1.85–29.01 Mb; longest contig 2.02–171.62 Mb), graph-based pan-genome variant sets (11.57 M variants including 60 K structural variants), and 5-methylcytosine sites (14.68%–27.05% of the CpG sites). We also identified several severe chromosome aberration events, which would result from chromosome break and fusion events. Our cancer genome assemblies will provide unprecedented resolution to understand cancer genome instability and chromosomal aberration.